2001
DOI: 10.1562/0031-8655(2001)073<0257:atosmt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Antivascular Treatment of Solid Melanoma Tumors with Bacteriochlorophyll–serine-based Photodynamic Therapy¶

Abstract: We describe here a strategy for photodynamic eradica-tion of solid melanoma tumors that is based on photo-induced vascular destruction. The suggested protocol relies on synchronizing illumination with maximal circulating drug concentration in the tumor vasculature attained within the first minute after administrating the sensitizer. This differs from conventional photodynamic therapy (PDT) of tumors where illumination coincides with a maximal concentration differential of sensitizer in favor of the tumor, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…As a result, the efficacy of PDT can be lowered. In order to avoid the case when oxygen consumption becomes a limiting factor, fractionation of light enabling tissue re-oxygenation has been proposed [32][33][34][35]. Unfortunately, tumor tissue oxygenation exhibits a very heterogeneous response to PDT [36,37].…”
Section: Introduction -Parameters Influencing Photodynamic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the efficacy of PDT can be lowered. In order to avoid the case when oxygen consumption becomes a limiting factor, fractionation of light enabling tissue re-oxygenation has been proposed [32][33][34][35]. Unfortunately, tumor tissue oxygenation exhibits a very heterogeneous response to PDT [36,37].…”
Section: Introduction -Parameters Influencing Photodynamic Efficacymentioning
confidence: 99%
“…Unfortunately, tumor tissue oxygenation exhibits a very heterogeneous response to PDT [36,37]. For photosensitizers that have the vasculature as the main target [35,38,39], the supply of oxygen to tissue might be limited due to a vascular damage resulting from PDT. Occlusion of blood vessels and hypoxia can occur within a few minutes after beginning of PDT.…”
Section: Introduction -Parameters Influencing Photodynamic Efficacymentioning
confidence: 99%
“…In an attempt to tightly regulate ROS doses at temporal and spatial, as well as at type-specific levels, we made use of a bacteriochlorophyll-based (Bchl) photosensitizer Scherz et al, 2000;Scherz et al, 2001;Scherz et al, 2003) which allowed for controlled, in situ generation of ROS upon illumination at a wavelength matching its absorption spectrum. This compound and other bacteriochlorophyll-based molecules have been used for generation of cytotoxic levels of ROS in photodynamic therapy (PDT) of different malignancies Preise et al, 2003;Schreiber et al, 2002;Zilberstein et al, 2001) and for modeling superoxide dismutase activity (Ashur et al, 2003). The ROS profile generated by each sensitizer has been determined using electron spin resonance (ESR)-based analyses, time resolved optical spectroscopy and photochemical products analyses under cell-free conditions (Vakrat et al, 1999;Vakrat-Haglili et al, 2002;Vakrat-Haglili et al, 2005) and have been shown to include O 2 -, OH˙and singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral peaks of absorption for these PS are about 770-780 and 750-760 nm, respectively. The possibility of using these agents for PDT of melanoma [15], prostatic cancer [9], and some other tumors is intensely investigated. However, modern technology of preparing these PS is very difficult.…”
mentioning
confidence: 99%
“…The efficiency of PDT with bacteriophyllide serine [3,15] and palladium bacteriopheophorbide [9] was studied. Spectral peaks of absorption for these PS are about 770-780 and 750-760 nm, respectively.…”
mentioning
confidence: 99%